Responses of Jatropha curcas L. to water stress - Kevin Muyang Tawie, anak Sulok (Universiti Malaysia Sarawak, (UNIMAS), 2010)
Research on production of Jatropha curcas focus mainly on its suitability to dry and and lands; whereas less attention has been paid to its production under high water availability. The growth performance of a drought tolerant plant such as J. curcas under different watering regimes was studied to investigate the influence of both high and reduced water availability on the various morphological and physiological traits that could contribute to an understanding of the effects of water stress on the plant. The experiment was a completely randomized design (CRD) with 4 treatments replicated 3 times )Each replicate consisted of 2 plants with a total of 24 plants altogether. Treatments were: (i) Rainfed (WO) - Plants watered at field capacity > -0.03 MPa, (ii) Mild water stress (W1) - Water maintained at soil water potential between > -0.10 and > -0.30 MPa, (iii) Moderate water stress (W2) - Water maintained at soil water potential between > -0.80 and > -1.0 MPa, and (iv) Extreme water stress (W3) - Water maintained at soil permanent wilt point >-1.50 MPa. The well-watered plants responded by showing significantly (p < 0.05) better height, greater proportion of inflorescence and fruits, comparatively larger fruits and more mass in seeds, higher leaf stomatal density and bigger leaf area growth. Number of inflorescences, amount of fruits, fruit size, seeds mass, and leaf stomatal density were increased by 31,54,90,3, and 69 % respectively in plants grown under well-watered conditions. Photosynthesis rates (A), stomatal conductance (gs), and transpiration (E) of the control was significantly (p < 0.05) higher than its water-stressed counterparts. However, water use efficiency for WO and W3 showed insignificant difference probably due to W3 adaptive capability to water deficits. Strong correlations were established between leaf stomatal conductance with both photosynthetic rates (r2 = 0.86) and volumetric soil water content (r2 = 0.89). Furthermore, foliar abscisic acid (ABA) was significantly correlated to stomatal conductance (r2 = 0.96) and volumetric soil water content (r2 = 0.83). Extreme water stress increased foliar ABA by 5-folds which in turn reduced stomatal conductance and thus decreasing photosynthesis rates. As an indicator for water stress, foliar spectral analysis showed low reflectance which attributed primarily to absorption by higher concentration of chlorophyll photosynthetic pigments and the presence of cytoplasmic fluid at the leaf cellular level. Strong significant I11 correlations were achieved by the reflectance indices such as the reflectance at 550 nm (R550)s, tructure independent pigment index (SIPI), and photochemical reflectance index (PRI) to leaf photosynthetic pigments indicating the depression caused by drought to chlorophyll concentrations in leaves. Overall, the well-watered plants at soil water field capacity (-0.03 MPa) showed better morphological and physiological responses whereby the positive effect has been very favaourable in terms of its flowering and fruiting due to the plant's potential to produce biofuel.